Research advances of HarvestPlus socioeconomic studies in LAC - Gonzáles, C. (2014)
The socioeconomic area of HarvestPlus LAC seeks to generate information to guide the decision related to biofortified crops in the region. The idea of this seminar is to present advances made in three socioeconomic studies: a. Potential departments/regions for an intervention with biofortified crops (cassava, rice, beans and maize) in Colombia; b. Adoption, consumption and commercialization of improved rice varieties in Bolivia and c. Preliminary results of a consumer acceptance of a High Iron Bean variety (Super Chiva) in Guatemala.